Structure of the human‐heart fatty‐acid‐binding protein 3 in complex with the fluorescent probe 1‐anilinonaphthalene‐8‐sulphonic acid. (1st October 2013) - Hirose, Mika; Sugiyama, Shigeru; Ishida, Hanako; Niiyama, Mayumi; Matsuoka, Daisuke; Hara, Toshiaki; Mizohata, Eiichi; Murakami, Satoshi; Inoue, Tsuyoshi; Matsuoka, Shigeru; Murata, Michio
<x xml:space="preserve">Abstract</x> Heart‐type fatty‐acid‐binding protein (FABP3), which is a cytosolic protein abundantly found in cardiomyocytes, plays a role in trafficking fatty acids throughout cellular compartments by reversibly binding intracellular fatty acids with relatively high affinity. The fluorescent probe 1‐anilinonaphthalene‐8‐sulfonate (ANS) is extensively utilized for examining the interaction of ligands with fatty‐acid‐binding proteins. The X‐ray structure of FABP3 was determined in the presence of ANS and revealed the detailed ANS‐binding mechanism. Furthermore, four water molecules were clearly identified in the binding cavity. Through these water molecules, the bound ANS molecule forms indirect hydrogen‐bond interactions with FABP3. The adipocyte‐type fatty‐acid‐binding protein (FABP4) exhibits 67% sequence identity with FABP3 and its crystal structure is almost the same as that of FABP3. However, FABP4 can bind with a higher affinity to ANS than FABP3. To understand the difference in their ligand specificities, a structural comparison was performed between FABP3–ANS and FABP4–ANS complexes. The result revealed that the orientation of ANS binding to FABP3 is completely opposite to that of ANS binding to FABP4, and the substitution of valine in FABP4 to leucine in FABP3 may result in greater steric hindrance between the side‐chain of Leu115 and the aniline ring of ANS.